Rancangan Sistem Pendeteksi Pencurian Helm Menggunakan Protokol MQTT Dan Bluetooth HC-05 Berbasis Arduino - Fadolly Aryaviocholda; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The most vehicles used by college students is motorcycle. College students parking their motorcycle in the parking area provided by the campus. The parking area mostly does not have a helmet storage facility and parking attendants are not at all times can supervise so most college students put a helmet on the motorcyle. Based on data obtained from a research questionnaire made about about college students behavior when parking a motorcycle in a parking area conducted on 30 students at the Faculty of Computer Science Brawijaya get the conclusion that college students do not pay attention to their helmets security which resulted in 12 of 30 college students having experienced a helmet loss. Therefore in this research the made design of devices to prevent helmet theft by using magnetic reed switch sensors as lock helmet and connectivity between the master and slave Bluetooth HC-05 as a marker of the distance between the helmet and the motorcylce. MQTT communication protocol is used to send data from the system device to the Adafruit IO broker then the data is sent to the user's android application.Sending data from the system device to the Adafruit IO broker has a percentage of success that is 100% and an average delivery time of 2.1 seconds and sending time from Adafruit IO to the user application has an average delivery time of 1 second. The resulting output is a warning alarm when the helmet lock is open and when the distance between the helmet and the motorcycle is not at a safe distance. To provide information to the user successfully sending a notification